Relación del huerto escolar y el aprendizaje en el entorno natural en el subnivel II de la Unidad Educativa Fiscomisional “San Vicente de Paúl” en el periodo noviembre 2020 – abril del 2021 - Naula Delgado, Ruth Josefina (2021)
In actuality, the school garden has become a fundamental strategy within Educational Institutions. In fact, it has become a pedagogical tool, where creativity comes into play for learning and caring for the environment. Despite the circumstances that we have been experiencing as a result of this pandemic, we have sought alternatives to achieve learning in the natural environment of children in sublevel II of the aforementioned educational institution. This study was carried out through a critical analysis, which allowed setting the objectives. This is a descriptive investigation, so that a survey with 10 items, and 4 choices of response, was elaborated to collect information about the students' learning when interacting with a school garden. The population and sample were 24 students between boys and girls. The results obtained were represented graphically with their proper analysis and interpretation, thus allowing to identify the importance of school gardens in the learning of early childhood education children. Keywords: garden, learning, natural environment